Tablas gateway-a Odiongan seaport terminal - Rosales, Leoly F. (Manila : National University, 1999)
Philippines is one of the developing countries today. Those who are living far flung place will benefited despite that problem was only critical in contradictory Philippine Government, as already implementing sufficient policies or measures to mobilize our economy in order to get the so called hesitation in terms of their living conditions.